A Three-Wave Longitudinal Study of Moderated Mediation between Perceptions of Politics and Employee Turnover Intentions : The Role of Job Anxiety and Political Skills - Haider, Sajid (Colegio Oficial de Psicólogos de Madrid, 2020)
This study examined a longitudinal moderated mediation model for answering the question of how and why perceptions of organizational politics influence turnover intentions, and how employees' political skills are contingent upon this relationship by reducing job anxiety. Data were gathered in three waves from employees in the banking sector (N = 347). The results of multiple linear regression analyses indicate that job anxiety mediates the relationship between perceptions of politics and turnover intentions, and employees' political skills reduce turnover intentions by weakening the effect of perceptions of politics on job anxiety. This study contributes to human resource management and organizational psychology literature by explaining moderated mediation mechanisms through which perceptions of organizational politics affect employee turnover intentions.